Sifat Fisik, Kimia, dan Sensoris Es Krim Susu Kedelai dengan Penambahan Ekstrak Kayu Manis - Fuady Shobur; Wikanastri Hersoelistyorini; Yunan Kholifatuddin Syadi (Jurnal Pangan dan Gizi, 2021)
Soy milk is an alternative to cow's milk in ice cream making because it has almost the same protein content as cow's milk. The unpleasant smell of soy milk is a problem that often arises, so efforts are needed to cover it up. Cinnamon is known to give aroma so that it can suppress the unpleasant aroma of soy milk and can improve the resistance to melting and overrun of non-cow's milk ice cream. The purpose of this study was to determine the effect of the addition of cinnamon extract on the physical, chemical and sensory properties of soy milk ice cream. The variations in the addition of cinnamon extract were (0,1,3,5, and 7%). This research begins with making soy milk, making cinnamon extract and making ice cream. The resulting ice cream is analyzed for physical properties (overrun and melting resistance), chemical properties (protein content) and sensory properties (color, aroma, taste and texture). This research is an experimental type using a completely randomized design (CRD) monofactor with 5 treatments and 5 replications. The addition of 5% cinnamon extract is the best treatment with an overrun value of 3.09%, melting resistance 18.74 minutes / 10g, protein content of 6.72%, hedonic sensory properties of 3.01 (like). The results showed that the addition of cinnamon extract to soy milk ice cream had a significant effect on physical, chemical and sensory properties.